ONTOLOGICAL INTERPRETATION OF HUMAN–MACHINE RELATIONS IN CYBERPHILOSOPHY (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
Human–machine relations have become one of the central issues of contemporary cyberphilosophy due to the rapid development of artificial intelligence, digital communication, and cyber-physical systems. This article examines the ontological foundations of human–machine relations and analyzes how contemporary philosophical approaches conceptualize the interaction between humans and intelligent technologies. The study aims to explore the transformation of traditional boundaries between humans and machines and to identify emerging hybrid forms of existence within digital environments. The research employs conceptual analysis, postphenomenological interpretation, cybernetic ontology, and Human–Machine Communication (HMC) perspectives. The findings indicate that recent cyberphilosophical theories increasingly view humans and machines as interconnected participants in dynamic processes of communication, individuation, and coevolution. The analysis reveals that digital technologies not only mediate human experience but also actively contribute to the formation of identity, agency, and social reality. Furthermore, the study highlights ongoing debates concerning technological agency, moral responsibility, and the preservation of human autonomy in AI-mediated societies. It is concluded that understanding human–machine relations requires moving beyond traditional subject–object frameworks toward relational and process- oriented ontologies capable of explaining hybrid forms of existence in the digital age.
Keywords: Cyberphilosophy, human–machine relations, artificial intelligence, digital ontology, human–machine communication, postphenomenology, cybernetics, technological agency, hybrid ontology, digital society.